Rancangan Bangun Sistem Pendeteksi Kebocoran Gas LPG Menggunakan Nodemcu ESP866 Berbasis Internet - Raka Andriawan; Dhe Berliani; Yuliarman Sarigih; Ulinnuha Latifa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Abstract: This study aims to determine the design of an LPG gas leak detection system using Internet-based Nodemcu ESP866. LPG gas cylinders are an essential kitchen fuel for most people. In preparing the research, the authors first collected data by conducting a literature study to find out the schematic circuit, component datasheet, and how the components work. Based on statistical data from the fire department from January 2010 to August 24, 2010, there were 46 fire incidents in the DKI Jakarta area, with an estimated material loss of Rp. and many materials. With the results, we get from our tool. Namely, the Buzzer as an alarm, the LED as an indicator, and the DC Fan can be On when the sensor detects a leak in the gas cylinder. In conclusion, the tool can be integrated with a smartphone using Wifi. In testing the device, the measurement range is 5-30 meters. At a distance of 5 meters, it produces 4.76, and at a distance of 10 meters, the time difference is around 2 seconds slower for smartphones to receive notifications. At a distance of 20 meters, it produces 7.66 seconds; at a distance of 30 meters, the time difference is 2.5 seconds slower for smartphones to receive notifications. Keywords: NodeMCU Esp8266, Internet Of Things, Buzzer, Smartphone